An observational study of the hand hygiene initiative: a comparison of preintervention and postintervention outcomes. Issue 5 (22nd May 2013) - Mukerji, Amit; Narciso, Janet; Moore, Christine; McGeer, Allison; Kelly, Edmond; Shah, Vibhuti
Abstract : Objectives: To evaluate the impact of implementing a simple, user-friendly eLearning module on hand hygiene (HH) compliance and infection rates. Design: Preintervention and postintervention observational study. Participants: All neonates admitted to the neonatal intensive care unit (NICU) over the study period were eligible for participation and were included in the analyses. A total of 3422 patients were admitted over a 36-month span (July 2009 to June 2012). Interventions: In the preintervention and postintervention periods (phases I and II), all healthcare providers were trained on HH practices using an eLearning module. The principles of the '4 moments of HH' and definition of 'baby space' were incorporated using interactive tools. The intervention then extended into a long-term sustainability programme (phase III), including the requirement of an annual recertification of the module and introduction of posters and screensavers throughout the NICU. Primary and secondary outcome measures: The primary outcome was HH compliance rates among healthcare providers in the three phases. The secondary outcome was healthcare-associated infection rates in the NICU. Results: HH compliance rates declined initially in phase II then improved in phase III with the addition of a long-term sustainability programme (76%, 67% and 76% in phases I, II and III, respectively (p<0.01). Infection rates showed an opposing, but concomitant trend in the overall population as well as in infants <1500 g and were 4%, 6% and 4% (p=0.02), and 11%, 21% and 16% (p<0.01), respectively, during the three phases. Conclusions: Interventions to improve HH compliance are challenging to implement and sustain with the need for ongoing reinforcement and education.